Integrated principles of zoology - Hickman, Cleveland P. 4 0 16; 1935- , Roberts, Larry S.,;Larson, Allan; 5 (Boston : McGraw-Hill, 2001)
A college text for introductory zoology courses that describes the diversity of animal life and the adaptations that enable animals to inhabit nearly all conceivable ecological niches.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Zoology; 20; 2